Perlindungan Hukum bagi Anak dan Perempuan dalam Rancangan Kitab Undang-undang Hukum Pidana (RKUHP) Indonesia - Asmin Fransiska (Jurnal Perkotaan, 2017)
Woman and children are the most vulnerable groups that should be protected under the law and policies. However, in the practices level, those groups are being ignored and to some extend the law and policies are created to deprive their rights. The violence as well as the limitation of rights has leaded women and children to face multi layers of violence. Indonesia government and legislative are processing the draft of Indonesian Penal Code (Rancangan Kitab Undang-Undang Hukum Pidana-RKUHP). Under the draft of the Penal Code, there are some articles that should be scrutinize in order to ensure that the right of women and children will be protected and not being eliminated. Therefore, this article aims to elaborate what is the issue in Indonesia Penal Code draft that should be taken into consideration and what should be done in order to create more proper formulation of the law that protect women and children rights. The method that has been used is a literarure review and normarive approach with human rights perspective.